Influence of alloying elements on hot corrosion resistance of nickel-based single crystal superalloys coated with Na2SO4 salt at 900 °C. (1st January 2021) - Song, Peng; Liu, Mingfeng; Jiang, Xiangwei; Feng, Yuchao; Wu, Junjie; Zhang, Gong; Wang, Dong; Dong, Jiasheng; Chen, Xing-Qiu; Lou, Langhong
Abstract: Hot corrosion behavior of three nickel-based single crystal superalloys with different key alloying elements (including Re, Cr, Al and Ti) contents in molten Na2 SO4 salt at 900 °C was investigated. Comparative study of hot corrosion resistance was conducted on two Re -free superalloys with 12 wt% Cr and different content of Al and Ti. By further adding Re, the experimental alloy with moderate Cr content (8.5 wt%) and Al/Ti > 1 in the present research also exhibited excellent hot corrosion resistance. The influence mechanism of Re on promoting hot corrosion resistance was attempted to be explored in combined with first-principle calculation. In addition, the potential design space of new-developed single crystal superalloys was also proposed. Graphical abstract: Unlabelled Image Highlights: Hot corrosion resistance of single crystal superalloys significantly depended on the ratio of Al/Ti in terms of the formation of a compact and protective NiTiO3 layer. Re significantly improved hot corrosion resistance of the experimental single crystal superalloy. The influence mechanism that adding Re may facilitate diffusion of Cr in γ phase and diffusion of Ti in γ' phase had been explored in combined with first-principle calculation. Potential design space for developing new type of hot corrosion resistant single-crystal superalloys was proposed.